1545 (The Court and Reign of Francis the First, King of France, 2014)
Pediatric very rare tumors (VRTs) are a highly heterogeneous group of neoplasms defined by an annual incidence of <2 cases per million children under 18 years. Their rarity precludes prospective clinical trials, resulting in limited evidence-based guidelines and largely individualized treatment approaches. Olfactory neuroblastoma (ON) is an exceptionally rare pediatric VRT arising from the olfactory neuroepithelium, typically affecting adults. In children, ON is locally aggressive and may present with regional or distant metastases. Prognosis depends on stage, histology, and multimodal treatment. Owing to the absence of pediatric-specific guidelines, this project aims to develop internationally harmonized consensus recommendations for diagnosis and management.